Answer:
12
Step-by-step explanation:
-12 = -3/4x + 3
-9 = -3/4x
-9 = (-3/4) times x
-9 = (-3/4) times 12
hope this helps! :)
Answer: 9
x
3
(
5
x
+
8
)
Step-by-step explanation:
Factor 9
x
3 out of 45
x
4
+
72x
3
.
Answer:
B
) Negative
Step-by-step explanation:
Given the expression 3xy
when x>0 and y<0
The value of the expression 3xy will be negative.
This is because the product of a positive and negative number will always be negative.
For illustration,
Let x=5>0 and y=-5<0
3xy=3(5)(-5)=-75
NOTE:
![-X-=+\\-X+=-\\+X+=+](https://tex.z-dn.net/?f=-X-%3D%2B%5C%5C-X%2B%3D-%5C%5C%2BX%2B%3D%2B)
Answer:
x = -1, y = -2.
Step-by-step explanation:
Using the elimination method,
multiply the first eqn by 2 and the 2nd eqn by 5.
6x - 10y = 14
25x - 10y = -5
Subtract one of the new equations from the other
-19x = 19
x = -1
Sub x=-1 into the 2nd eqn
-5 - 2y = -1
y = -2
Hence x = -1, y = -2.
Answer:
0
Step-by-step explanation:
If you think in degrees easier than in radians, then make this conversion.
pi = 180 degrees
(3/2)*pi = (3/2) * 180 = 180 * 3/2 = 270
Sin(270) = -1
cos(270) = 0
==========
sin(270) * cos(270) = -1 * 0 = 0